2020
DOI: 10.1097/j.pain.0000000000001879
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T cells counteract neuropathic pain through inhibition of the Th1 response at the site of peripheral nerve injury

Abstract: The inflammatory/immune response at the site of peripheral nerve injury participates in the pathophysiology of neuropathic pain. Nevertheless, little is known about the local regulatory mechanisms underlying peripheral nerve injury that counteracts the development of pain. Here, we investigated the contribution of regulatory T (Treg) cells to the development of neuropathic pain by using a partial sciatic nerve ligation model in mice. We showed that Treg cells infiltrate and proliferate in the site of periphera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 93 publications
2
36
0
Order By: Relevance
“…In the setting of injury, inflammatory signaling at multiple access points (e.g., injury site, nerve, and DRG) activates nociceptive circuits 37. However, our finding that intrathecal activation of myeloid cells is sufficient to activate meningeal immunity raises the possibility that modulating the meninges is a potential therapeutic avenue of neuropathic pain management, by suppressing meningeal Treg expansion-mediated microglial activation or by the release of intrathecal immune modulators that override peripheral inflammatory cues. Given that human genetic analyses and other studies indicate a contribution of Tregs and their dominant cytokines in neuropathic and inflammatory pain models [38][39][40][41][42][43] , further investigations of Treg localization and impact on microglia will be relevant to understanding the generation and conceivably the treatment of nerve-injury-induced chronic pain. purchased from The Jackson Laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…In the setting of injury, inflammatory signaling at multiple access points (e.g., injury site, nerve, and DRG) activates nociceptive circuits 37. However, our finding that intrathecal activation of myeloid cells is sufficient to activate meningeal immunity raises the possibility that modulating the meninges is a potential therapeutic avenue of neuropathic pain management, by suppressing meningeal Treg expansion-mediated microglial activation or by the release of intrathecal immune modulators that override peripheral inflammatory cues. Given that human genetic analyses and other studies indicate a contribution of Tregs and their dominant cytokines in neuropathic and inflammatory pain models [38][39][40][41][42][43] , further investigations of Treg localization and impact on microglia will be relevant to understanding the generation and conceivably the treatment of nerve-injury-induced chronic pain. purchased from The Jackson Laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…While it is known that CD8 + cytotoxic T cells are recruited to peripherally injured nerves, responding to elevated antigen-presenting MHC class I molecules, the precise mechanism underlying this process remains unclear ( [122,123]; reviewed in [124]). It was recently shown that Treg cells also play a role at the site of a peripheral nerve injury, counteracting neuropathic pain by inhibiting Th1 cell-mediated responses [125], and it has been reported that there is a disrupted Th17/Treg balance in patients with chronic low back pain [126].…”
Section: At the Site Of The Peripherally Injured Sciatic Nerve And Asmentioning
confidence: 99%
“…Proinflammatory cytokines have been associated with neuropathic pain, and anti-inflammatory cytokine potentiation was thought to alleviate neuropathic pain [ 19 , 20 ]. Some publications have focused on T cells, which are considered key players of the adaptive immune system [ 21 , 22 ]. Th1 has been shown to mediate neuropathic pain [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mice lacking IFN-γ have been shown to have less mechanical sensitivity [ 28 ]. Treg cells [ 21 ] have also recently been the focus of attention of researchers. It has been shown that Treg cells are involved in endogenous healing [ 29 ] and that there is an increase in Treg cells in PHN [ 18 , 29 ].…”
Section: Introductionmentioning
confidence: 99%